2020
DOI: 10.24275/rmiq/bio1605
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis, optimization and characterization of ZnO nanoparticles using Bacillus cereus MN181367 and their antimicrobial activity against multidrug resistant bacteria

Abstract: totales del petróleo intemperizados en suelos y sedimentos (Biodegradation modeling of sludge bioreactors of total petroleum hydrocarbons weathering in soil and sediments)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…The two peaks disappeared in the synthesised NPs and new peaks were observed that suggest the synthesis of ZnO and nickel doped ZnO NPs. The absorption peaks were observed in the wavelength range of 350–380 nm [ 33 ], and indicated the synthesis of ZnO and nickel doped ZnO nanoparticles. It is also strongly believed that the phytochemicals like phenols, phenolic, steroids and tannins are working as reducing agents and are responsible for conversion of metal salts into ZnO nanoparticles [ 17 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…The two peaks disappeared in the synthesised NPs and new peaks were observed that suggest the synthesis of ZnO and nickel doped ZnO NPs. The absorption peaks were observed in the wavelength range of 350–380 nm [ 33 ], and indicated the synthesis of ZnO and nickel doped ZnO nanoparticles. It is also strongly believed that the phytochemicals like phenols, phenolic, steroids and tannins are working as reducing agents and are responsible for conversion of metal salts into ZnO nanoparticles [ 17 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several microbes have been used for ZnO-NP synthesis, but bacteria are most preferred due to their genetic manipulation capability and ease of handling over other eukaryotic microbes (Jayabalan et al, 2019;Iqtedar et al, 2020;Ahmed et al, 2021). The reproducible bacteria (like lactic acid producing bacteria) have gained more interest in bacterial-mediated NP synthesis because of their high production of diverse enzymes and non-pathogenic nature.…”
Section: Bacterial-mediated Zno-np Synthesismentioning
confidence: 99%
“…The release of Zn 2+ ions on the biomolecules (DNA/ proteins/ enzymes) found in bacterial cells is one of the major antibacterial mechanisms. It is well known that the formed ZnO-NPs disrupt numerous bacterial cell functions such as metabolism, active transport, and enzyme activity and subsequently induce bacterial cell death (Rauf et al, 2017;Taran et al, 2018;Iqtedar et al, 2020).…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Accordingly, existing antibiotic medications can be superseded with biomaterials including herbal medicine with high antimicrobial, antiviral, and antioxidant activity. 5,6 Mangifera Indica (Mango) is a popular tropical fruit in the world 7 and contains substances such as phenol constituents, triterpenes, flavonoids, phytosterols, and polyphenols. 2 The entire plant, including the leaves, fruit, roots, and flowers, has various therapeutic characteristics used for centuries to cure various illnesses.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, existing antibiotic medications can be superseded with biomaterials including herbal medicine with high antimicrobial, antiviral, and antioxidant activity. 5,6…”
Section: Introductionmentioning
confidence: 99%